PAUL FEYERABEND ON THE SCIENTIFIC WORLDVIEW: TOWARDS QUESTIONING THE SCIENTIFIC UNIFORMITY - N. I. Petrunok (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the following article is to draw attention to main problems of scientific values as they were stated by Paul Feyerabend. Various philosophers and epistemologists have always tried to prove chosen principles and objectives, but only few dared to jeopardize their fundamentals. Stereotypes of searching for ultimate truth ceased to hold; however, scientific coordinates are still not qualified. Underlying ambiguities often remain unarticulated. Among those who ventured to shed light on them were the philosophers of post-positivistic branch. One of those who questioned science values in social, cultural, and philosophical approaches the most rigidly was Paul Feyerabend. By means of typical political concepts (such as ideology and propaganda) he detected basic objectives of scientists. Our main methodological tools in this research are comparative analyses of the sources and immanent critique of Feyerabend’s arguments. The scientific novelty is based on our core objective to clarify substantial obstacles for homogeneity of science. Does such homogeneity or unity exist at any level? Feyerabend’s answer is a weak “yes”. He accepts such unity only as a useful assumption or a myth. In one of his latest books, Conquest of Abundance, he calls it a “flag” for the “people doing science.” As Feyerabend diagnosed faults of relativism, instrumentalism, and realism – all of them are threatened by the same menace of being invalid to response the world “at face value” – we have to deal somehow with topics denounced by him. In conclusion, we show important implications for the creation of a specific worldview at the intersection of philosophy and science. Considering a number of negatives, in the article we elicit fruitful ideas of Feyerabend, and contextually question them without resorting to a superficial reproach.